Structure-Property Relationships for a Series of Ruthenium(II) Polypyridyl Complexes Elucidated through Raman Spectroscopy - Luke O’Neill; Laura Perdisatt; Christine O’Connor (Journal of Spectroscopy)
A series of ruthenium polypyridyl complexes were studied using Raman spectroscopy supported by UV/Vis absorption, luminescence spectroscopy, and luminescence lifetime determination by time-correlated single photon counting (TCSPC). The complexes were characterised to determine the influence of the variation of the conjugation across the main polypyridyl ligand. The systematic and sequential variation of the main polypyridyl ligand, 2-(4-formylphenyl)imidazo[4,5-f][1,10]phenanthroline (FPIP), 2-(4-cyanophenyl)imidazo[4,5-f][1,10]phenanthroline (CPIP), 2-(4-bromophenyl)imidazo[4,5-f][1,10]phenanthroline (BPIP), and 2-(4-nitrophenyl)imidazo[4,5-f][1,10]phenanthroline (NPIP) ligands, allowed the monitoring of very small changes in the ligands electronic nature. Complexes containing a systematic variation of the position (para, meta, and ortho) of the nitrile terminal group on the ligand (the para being 2-(4-cyanophenyl)imidazo[4,5-f][1,10]phenanthroline (p-CPIP), the meta 2-(3-cyanophenyl)imidazo[4,5-f][1,10]phenanthroline (m-CPIP) and 2-(2-cyanophenyl)imidazo[4,5-f][1,10]phenanthroline (o-CPIP)) were also characterised. Absorption, emission characteristics, and luminescence yields were calculated and correlated with structural variation. It was found that both the electronic changes in the aforementioned ligands showed very small spectral changes with an accompanying complex relationship when examined with traditional electronic methods. Stokes shift and Raman spectroscopy were then employed as a means to directly gauge the effect of polypyridyl ligand change on the conjugation and vibrational characteristics of the complexes. Vibrational coherence as measured as a function of the shifted frequency of the imizodale bridge was shown to accurately describe the electronic coherence and hence vibrational cooperation from the ruthenium centre to the main polypyridyl ligand. The well-defined trends established and elucidated though Raman spectroscopy show that the variation of the polypyridyl ligand can be monitored and tailored. This allows for a greater understanding of the electronic and excited state characteristics of the ruthenium systems when traditional electronic spectroscopy lacks the sensitivity.